DESAIN LOGO SEBAGAI STRATEGI IDENTITAS VISUAL DAN PROMOSI INSTITUSIONAL: STUDI KASUS PROGRAM STUDI DKV UHN SUGRIWA - I Putu Adi Saskara; Ida Bagus Komang Sindu Putra; I Putu Adi Natha; Ida Bagus Putu Adi Pratama (Tanra: Jurnal Desain Komunikasi Visual Fakultas Seni Dan Desain Universitas Negeri Makassar, 2026)
This study examines logo design as a strategic instrument for visual identity and institutional promotion within newly established academic programs. Using a descriptive qualitative approach, data were collected through documentation, visual observation, and semi-structured interviews with the logo designer and program administrators. Analysis was conducted using visual identity theory, design semiotics, and institutional branding frameworks. The findings show that the logo of the Visual Communication Design Study Program at UHN Sugriwa successfully integrates cultural values, academic vision, and local philosophical meanings into its visual elements—shape, color, and typography. The design reflects the institutional narrative inspired by I Gusti Bagus Sugriwa and effectively builds a distinctive, culturally grounded identity. Furthermore, the logo functions as a strategic communication tool that strengthens institutional credibility and enhances promotional efforts aimed at prospective students. This study contributes to the discourse on culturally grounded identity design in higher education and highlights the role of logo design as a strategic component of institutional branding.